Effects of inflation on foreign direct investment in Nigeria - Njoku, Charles Odinakachi; Nwaimo, Chilaka Emmanuel; Essienette, Ima-Obong Bassey (Journal of Commerce, Management, and Tourism Studies, 2023)
Inflation's effects on the volume of foreign direct investment (FDI) in Nigeria from 1995 to 2020 are examined in this study. In order to establish the relationship between the dependent variable (foreign direct investment) and the independent variables (inflation, real interest rate, and exchange rate), secondary data were gathered from the CBN Statistical Bulletin, Nigeria Bureau of Statistics and the World Bank Database. Johansen cointegration test was used to ascertain the long-term relationship between FDI and the independent variables, while the enhanced Dicker-Fuller test (ADF) was used to examine the data's time series property. It was decided to use the Vector Error Correction Model (VECM), and the error coefficient, which is correctly signed and significant, shows that the independent variables and FDI have a long-term relationship. The model's explanatory variables' effects on FDI were statistically insignificant. But as indicated by the probability of the F-statistic at the 5% level of significance, the overall regression was significant. The study suggests that efforts be made to use additional macroeconomic policies as a way to boost foreign direct investment in the economy and that the government and monetary authorities should not solely rely on the tool and model for controlling inflation.